"My Conscience is Free and Clear": African-Descended Women, Status, and Slave Owning in Mid-Colonial Mexico. Issue 3 (10th July 2018) - Williams, Danielle Terrazas
Abstract : On March 8, 1679, Polonia de Ribas entered her last will and testament into record at the offices of Alonso de Neira Claver, the royal notary public of Xalapa. The will included information about Polonia's family, possessions, debts to be collected, and how she wanted her estate distributed after her passing. She was well acquainted with the appropriate processes and venues to ensure that such matters were officially acknowledged. In the second half of the seventeenth century, Polonia demonstrated her legal acumen by documenting half a dozen transactions with the notary public in Xalapa.